Life satisfaction and income inequality - Paolo Verme (Bar-Ilan University, Department of Economics, 2010)
Do people care about income inequality and does income inequality affect subjective well-being? Welfare theories can predict either a positive or a negative impact of income inequality on subjective well-being and empirical research has found evidence on a positive, negative or non significant relation. This paper attempts to determine some of the possible causes of such empirical heterogeneity. Using a very large sample of world citizens we test the consistency of income inequality in predicting life satisfaction. We find that income inequality has a negative and signifcant effect on life satisfaction. This result is robust to changes of regressors and estimation choices and also persists across different income groups and across different types of countries. However, this relation is easily obscured or reversed by multicollinearity generated by the use of country and year fixed effects. This is particularly true if the number of data points for inequality is small, which is a common feature of cross-country or longitudinal studies.
Keywords: D63; I31; 330; happiness; inequality; Einkommensverteilung; Soziale Ungleichheit; Zufriedenheit; Welt